O assistente social na supervisão técnica de convênios entre o poder público e as organizações privadas de assistência social - Cardoso, Maria Helena Célia (2014)
The object of study of this work concerns the performance of social workers in the technical supervising of social assistance services provided by private organizations of social assistance under partnerships with the government through the Administration of Social Assistance and Development. The subjects chosen for this investigation are eight social workers who work as technical supervisors in the South, East and West Central areas of São Paulo city. The choice of these subjects was carried out for representing the technical supervisors which work in those five administrative areas. The interviewed professionals concurred with their narratives in order to demonstrate the hypotheses regarding: A) the real working conditions of technical supervisors: training, work pace, human resources; B) the recognition of technical supervisor mediation in the partnership between the state and the social assistance organizations, throwing light on the solving technical capacity; C) the tools used in technical supervision. Concerning specific objectives, it was possible to characterize the work accomplished by the social worker and to think over the meaning of technical supervision for the qualitative achievement of its purposes. The overseen social assistance services, under indirect public management, were gather together and listed, considering their respective typologies, as well as the number of CRAS and CREAS located according to São Paulo administrative districts, in order to demonstrate the territorial scope of these services that hold together the social assistance grid through the work of the technical supervisor. The conceptual and legal normative benchmark is based on the laws, ordinances and regulations of the National and Municipal Social assistance policies, and the analysis is founded on a critical perspective of the knowledge of the social assistance area